Analisis Pengaruh Teknik Think Pair Share dan Minat Membaca Terhadap Kemampuan Menulis Eksposisi pada Taruna Akademi Maritim Cirebon - Fathul Hidayati; Kamaludin Kamaludin (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
The aims of this study was to analyze the differences in the exposition writing skills of cadets who taught with the think-pair-share technique and reading interest cadets.This study used an experimental method, in which the experimental group was given treatment with the think-pair-share technique, while the control group was taught without the think-pair-share technique. The two groups were further differentiated based on groups with high and low reading interest. The population in this study were cadets’ level 1 in the first semester at the Cirebon Maritime Academy in the academic year of 2020/2021. The samples are cadets of Nautika 1 as the control class and cadets of Nautika 2 as the experimental class with 25 cadets each. Exposition writing ability data were collected through an exposition writing test while reading interest data were collected by filling out a reading interest questionnaire. The data analysis used was ANOVA with the help of the SPSS program.The conclusion in this study is that the exposition writing ability of cadets who have taught using the think-pair-share technique is better than cadets who taught without it. The exposition writing ability of cadets who have a high reading interest is better than cadets who have a low reading interest. There is an interaction between learning techniques and reading interest in influencing the ability to write exposition.